2019
DOI: 10.1111/jcmm.14855
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 dysregulation: Potential biomarkers predicting prognosis and guiding treatment choice in acute myeloid leukaemia

Abstract: Accumulating studies have proved EZH2 dysregulation mediated by mutation and expression in diverse human cancers including AML. However, the expression pattern of EZH2 remains controversial in acute myeloid leukaemia (AML). EZH1/2 expression and mutation were analysed in 200 patients with AML. EZH2 expression was significantly decreased in AML patients compared with normal controls but not for EZH1 expression. EZH2 mutation was identified three of the 200 AML patients (1.5%, 3/200), whereas none of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Differential expression analysis for RNA/miRNA sequencing data was calculated using the raw read counts with the R/Bioconductor package “edgeR”, all analyses were controlled for the false discovery rate (FDR) by the Benjamini–Hochberg procedure [ 24 ]. The miRNA which could target LEP was identified by the venn analysis ( http://bioinformatics.psb.ugent.be/webtools/Venn/ ) of three websites miRDB ( http://mirdb.org/miRDB/ ), miRWalk ( http://mirwalk.umm.uni-heidelberg.de/ ) and TargetScan ( http://www.targetscan.org/vert_72/ ) [ 25 , 26 ]. All basic statistical analyses were performed using the base functions in R version 3.4 ( https://www.r-project.org ).…”
Section: Methodsmentioning
confidence: 99%
“…Differential expression analysis for RNA/miRNA sequencing data was calculated using the raw read counts with the R/Bioconductor package “edgeR”, all analyses were controlled for the false discovery rate (FDR) by the Benjamini–Hochberg procedure [ 24 ]. The miRNA which could target LEP was identified by the venn analysis ( http://bioinformatics.psb.ugent.be/webtools/Venn/ ) of three websites miRDB ( http://mirdb.org/miRDB/ ), miRWalk ( http://mirwalk.umm.uni-heidelberg.de/ ) and TargetScan ( http://www.targetscan.org/vert_72/ ) [ 25 , 26 ]. All basic statistical analyses were performed using the base functions in R version 3.4 ( https://www.r-project.org ).…”
Section: Methodsmentioning
confidence: 99%
“…5 a, b and Additional file 3 : Table S2). The top 50 upregulated genes including CDH1 and the top 50 downregulated genes such as H19 were significantly associated with prognosis in AML by our previous studies [ 29 , 30 ]. In addition, the GO (Gene Ontology) analysis demonstrated that these DEGs involved in biologic processes, including multicellular organismal process, system development, multicellular organism development, and biological adhesion (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…What is more, our findings regarding the deregulated expression of EZH2 in AML agree with previous reports, suggesting that its overexpression (apart from mutation) promotes cell proliferation in hematologic and other malignancies. EZH2 controls the expression of genes involved in stem cell maintenance and differentiation and its down-regulation inhibits apoptosis, affects the expression of MAD2 and CDC20, and promotes chromosomal instability in AML cells [ 87 , 88 , 89 , 90 , 91 , 92 ]. Our findings also highlight the deregulated expression of SUZ12, another component of PRC2, responsible for the transcriptional repression of genes via methylation [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%